Adipose Derived Mesenchymal Stem Cells Restore Spermatogenesis in Male non Obstructive Azoospermia (Literature Review) - Tamadon, A.; Askarov, M.B.; Zhanbyrbekuly, U.; Zhankina, R.A.; Saipiyeva, D.T.; Ibragimov, A.K.; Kadirova, B.E.; Yessenuly, A.; Sherkhanov, R.S.; Suleiman, M.A. (Biomedical Chemistry: Research and Methods, 2021)
Stem cells are considered as new much promising therapeutic agents in treatment of male infertility due to their high differentiation potential and unlimited supply. In this review we summarized current views on application of mesenchymal stem cells in reproductive medicine.